A dose-finding study with TAK-442, an oral factor Xa inhibitor, in patients undergoing elective total knee replacement surgery - Weitz, Jeffrey I.; Cao, Charlie; Eriksson, Bengt I.; Fisher, William; Kupfer, Stuart; Raskob, Gary; Spaeder, Jeffrey; Turpie, Alexander G. G. (Thrombosis and Haemostasis, 2010)
This multicentre dose-finding study compared TAK-442, an oral factor Xa inhibitor, with enoxaparin for thromboprophylaxis after knee arthroplasty. In this parallel group study, patients were randomised to oral TAK-442 (40 or 80 mg once-daily [QD] or 10, 20, 40, or 80 mg twice-daily [BID] started 6–8 hours postoperatively), which was blinded as to dose, or to open-label subcutaneous enoxaparin (30 mg BID starting 12–24 hours postoperatively) for 10 days. Treatments were continued until bilateral venography was performed (maximum of 14 days). The primary efficacy endpoint was the composite of any deep-vein thrombosis, non-fatal pulmonary embolism or all-cause mortality, while the primary safety endpoint was major bleeding. Of 1,038 patients randomised who received at least one dose of study drug, 949 completed the study and 730 (76.9%) were evaluable for the primary efficacy analysis. Recruitment into the 10 and 20 mg BID dose groups was stopped early because the incidences of the primary efficacy endpoint were significantly higher than that with enoxaparin. The primary efficacy endpoint occurred in 22.0% of patients given enoxaparin and in 39.0%, 38.4%, 23.5%, 21.4%, 26.8%, and 14.3% of those receiving TAK-442 10 mg BID, 20 mg BID, 40 mg QD, 40 mg BID, 80 mg QD, and 80 mg BID, respectively. The incidences of major and clinically relevant non-major bleeding with TAK-442 were not dose-dependent or different from that with enoxaparin. All TAK-442 doses except 10 and 20 mg BID displayed similar efficacy and safety profiles to enoxaparin.
Keywords: Oral factor Xa inhibitor; anticoagulants; thromboprophylaxis; venous thromboembolism; total knee replacement